Association of psychological distress and work psychosocial factors with self-reported musculoskeletal pain among secondary school teachers in Malaysia - Zamri, E.N.; Moy, F.M.; Hoe, V.C.W. (Public Library of Science, 2017)
Background Musculoskeletal pain is common among teachers. Work-related psychosocial factors are found to be associated with the development of musculoskeletal pain, however psychological distress may also play an important role. Objectives To assess the prevalence of self-reported low back pain (LBP), and neck and/or shoulder pain (NSP) among secondary school teachers; and to evaluate the association of LBP and NSP with psychological distress and work-related psychosocial factors. Methods This was a cross-sectional study conducted among teachers in the state of Penang, Malaysia. The participants were recruited via a two stage sampling method. Information on demographic, psychological distress, work-related psychosocial factors, and musculoskeletal pain (LBP and NSP) in the past 12 months was collected using a self-administered questionnaire. Poisson regression was used to estimate the prevalence ratio (PR) for the associations between psychological distress and work-related psychosocial factors with LBP and NSP. Results The prevalence of self-reported LBP and NSP among 1482 teachers in the past 12 months was 48.0% (95% Confidence Interval (CI) 45.2%, 50.9%) and 60.1% (95% CI 57.4%, 62.9%) respectively. From the multivariate analysis, self-reported LBP was associated with teachers who reported severe to extremely severe depression (PR: 1.71, 95% CI 1.25, 2.32), severe to extremely severe anxiety (1.46, 95% CI 1.22, 1.75), high psychological job demand (1.29, 95% CI 1.06, 1.57), low skill discretion (1.28, 95% CI 1.13, 1.47) and poorer mental health (0.98, 95% CI 0.97, 0.99). Self-reported NSP was associated with mild to moderate anxiety (1.18, 95% CI 1.06, 1.33), severe to extremely severe anxiety (1.25, 95% CI 1.09, 1.43), low supervisory support (1.13, 95% CI 1.03, 1.25) and poorer mental health (0.98, 95% CI 0.97, 0.99). Conclusions Self-reported LBP and NSP were common among secondary school teachers. Interventions targeting psychological distress and work-related psychosocial characteristics may reduce musculoskeletal pain among school teachers.